Studi Penambahan Berbagai Jenis Tepung Terhadap Kualitas Starter Tempe Berdasarkan Parameter Lama Fermentasi - Agistiana Azzahra, Athiyya Nur; Al Toriq, Muhammad Rizki; Sari, Yuninda Anjar Firda (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2024)
Tempe starter is a collection of mold spores that have an important role in making tempe because they will affect the quality of the product. In the research conducted, several manipulations were used in the media material for making a starter using several bean mixtures as flour, which aims to compare the quality of the tempe starter and see the effect of adding various types of flour on the quality of the tempe starter made. This study used a completely randomized design (CRD) with 4 treatments and 5 replications. The control treatment was rice (100 g), the first treatment was rice (50 g) + green beans (50 g), the second treatment was rice (50 g) + mung bean (50 g), and the third treatment was rice (50 g). + green beans (25 g) + koro beans (25 g). The results of adding various types of flour to the quality of the tempe starter showed that the composition of the fastest mold growth was treatment 3 (50 g rice + 25 g green beans + 25 g mustard greens) for 31 hours and produced tempe physical properties with a typical white color of tempe. The compact texture does not break easily when sliced with a distinctive tempeh aroma with a combination of green bean and koro bean aromas without any ammonia smell.